Mapping of CGRP in the alpaca (Lama pacos) brainstem - de Souza E. (2008)
This work has been supported by the Ministerio de Educación y Ciencia (BFU2005-02241/BFI), Spain and by the CONCYTEC: PROCYT project 2006, Peru. The authors thank Ewing Rafael Duque for his technical assistance, N. Skinner for stylistic revision of the English text and Professor Gerard Tramu (University of Bordeaux I, France) for kindly providing the CGRP antiserum.